The epidemiology of tetracycline and ceftiofur resistance in commensal Escherichia coli - McGowan, Matthew Thomas (Kansas State University, 2014)
The modern phenomenon of increasing prevalence of antibiotic resistance in clinically relevant bacteria threatens humanity’s ability to use antibiotics to treat infection in both humans and animals. Despite the marked complexity of bacterial evolution, there is tremendous importance in unfolding the process by which antibiotic resistance genes emerge, disperse, and persist in the natural world. This thesis investigates certain aspects of this process in two experimental studies that differ primarily by scale but also by methodology. The first study examined the long-term annual prevalence of ceftiofur and tetracycline resistance in Canadian beef cattle from 2002 to 2011 at both phenotypic and genotypic levels. Ceftiofur was present at a very low prevalence (<4%) that did not statistically increase over the decade (p<0.05). Relative proportions of tetracycline genes tet(A), tet(B), and tet(C) also did not significantly change over the observation period. However, it was surprising that almost 20% of isolates recovered from nonselective agar harbored tet(C) given that current literature generally indicates that tet(C) is significantly less prevalent than tet(A) or tet(B). The usage of historical samples in addition to parallel selective plating using agar supplemented with antibiotics provided insight into systemic bias present in common microbial approaches. Long-term sample freezing significantly diminished the recoverability of E. coli over time. Additionally the usage of selective MacConkey agar containing tetracycline biased the proportions of tetracycline genes to over-represent the tet(B) gene in commensal E. coli compared to nonselective MacConkey agar. The second study attempted to explain the short-term selection effects of antibiotic treatment on the overall ecological fitness of commensal E. coli using bacterial growth parameters estimated from spectrophotometric growth curves as a simple surrogate of general fitness. Treating cattle with either tetracycline or ceftiofur was found to not only select in favor of tetracycline resistant bacteria, but also increased the overall fitness among the tetracycline resistant population. However, growth curves were unable able to explain why transiently selected resistant bacteria were eventually replaced by susceptible bacteria once the selection pressure was removed.
Keywords: Antimicrobial resistance; Growth curves; Tetracycline resistance; Ceftiofur resistance; Beef cattle; Epidemiology (0766); Microbiology (0410); Veterinary Medicine (0778)